Deteksi Cacing Nematoda pada Saluran Pencernaan Kambing Bligon di Desa Tahunan Grobogan Jawa Tengah: Detection of Nematode Worms in the Digestive Tract of Bligon Goat in the Tahunan village of Grobogan Central Java (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2021)
The purpose of this study was to determine the presence of  digestive tract nematodes  in the Bligon goat in the Tahunan village of Grobogan . There were 35 Bligon goats from Langgeng Makmur Farmer Group used for their feces to be sampled. Feed were given peanut straw and lamtoro. Qualitative examination was carried out using the Native method. The variables observed were the level of worm infection in goats and identification of worm eggs based on literacy The results shows that  It was detected that  as much as 60% of the bligo goats population in the Tahunan village of Grobogan have nematode worm eggs. Worms detected were Strongyloides sp. 34% while Trichuris sp. were 26% of 35 samples of Bligon goat feces. It was concluded that most of the Bligon goats are 60% detected by nematodes.Key words:        Bligon goat, nematode worms, Tahunan Grobogan Village